Flow features and micro-particle deposition in a human respiratory system during sniffing. (September 2018) - Calmet, H.; Houzeaux, G.; Vázquez, M.; Eguzkitza, B.; Gambaruto, A.M.; Bates, A.J.; Doorly, D.J.
Abstract: As we inhale, the air drawn through our nose undergoes successive accelerations and decelerations as it is turned, split and recombined before splitting again at the end of the trachea as it enters the bronchi. Fully describing the dynamic behaviour of the airflow and how it transports inhaled particles poses a severe challenge to computational simulations. In this paper we explore two aspects: the dynamic behaviour of airflow during a rapid inhalation (or sniff) and the transport of inhaled aerosols. The development of flow unsteadiness from a laminar state at entry to the nose through to the turbulent character of tracheal flow is resolved using accurate numerical models with high performance computing-based large scale simulations. Combining the flow solution with a Lagrangian computation reveals the effects of flow behaviour and airway geometry on the deposition of inhaled microparticles. Improved modelling of airflow and delivery of therapeutic aerosols could be applied to improve diagnosis and treatment. Abstract : Highlights: Micro-particle transport and deposition with unsteady flow in the human large airways during a rapid inhalation is proposed. Air Flow features under the sniff described in a human respiratory system.